The Role of Pragmatic Inferences in Interpreting Implicatures - Lubna Marqus Khoshaba; Misbah M.D. Al-Sulaimaan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
An inference is one of the pragmatic phenomena that has an important role in communication. It is defined as a process that leads to the interpretation of what a speaker or writer means or implicates. This study aims at studying the role of inferences in interpreting implicatures in literary texts. It hypothesizes that conversational implicatures cannot be interpreted unless they are contextualized and inferred. In this process, the reader or hearer relates intentions to what a speaker or writer means. So, the emergence of implicatures is related to the pragmatic inference that is considered reasonable conclusions. This research consists of four sections, (1) an introduction, (2) types of inference, (3) main distinctions between inferences, (4) relationship between an inference and literary texts, and (5) conclusions the study arrived at.